Sustainable Nanopozzolan Modified Cement: Characterizations and Morphology of Calcium Silicate Hydrate during Hydration - N. Mohamed, Sutan; I., Yakub; M. S., Jaafar; K. A., Matori; S. K., Sahari (Hindawi Publishing Corporation, 2015)
There are environmental and sustainable benefits of partially replacing cement with industrial by-products or synthetic materials in cement based products. Since microstructural behaviours of cement based products are the crucial parameters that govern their sustainability and durability, this study investigates the microstructural comparison between two different types of cement replacements as nanopozzolan modified cement (NPMC) in cement based product by focusing on the evidence of pozzolanic reactivity in corroboration with physical and mechanical properties. Characterization and morphology techniques using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDS), and scanning electron microscopy (SEM) were carried out to assess the pozzolanic reactivity of cement paste modified with the combination of nano- and micro silica as NPMC in comparison to unmodified cement paste (UCP) of 0.5 water to cement ratio (w/c). Results were then substantiated with compressive strength (CS) results as mechanical property. Results of this study showed clear evidence of pozzolanicity for all samples with varying reactivity with NPMC being the most reactive.